Educational Resource Management An international perspective - Glover, Derek (UCL Press, 2020)
The management of resources is a central duty for school and college leaders, but one for which they are often under-prepared. Good, contextual information and guidance are vital, especially as increased marketisation, international comparison and decentralised governance put additional pressure on leaders to manage their resources astutely. This second edition of Educational Resource Management: An International Perspective is an updated guide to all aspects of this key responsibility and how they are applied in today's real-world situations across the globe. Following a detailed overview of funding and resource management in public and private provision, the book looks at the criteria by which the effectiveness, efficiency and equity of the management of educational resources may be judged. It goes on to explore cost structures, budgets and the principles of asset management, all illustrated through case studies that draw on practitioner experiences and the authors' observations in a range of national contexts. Concluding with a review of current tensions in educational resource management and pointers towards further study, the book is a succinct yet comprehensive guide for school and college leaders. It will be essential reading for those studying the subject as part of Masters and Professional Doctorate qualifications.